2001
DOI: 10.1007/s002640100290
|View full text |Cite
|
Sign up to set email alerts
|

Modular megaprosthesis for distal femoral tumors

Abstract: We treated 48 patients with distal femoral tumors by resection and limb salvage with an uncemented megaprosthesis (Howmedica Modular Replacement System). Diagnoses included: 32 osteosarcomas, five chondrosarcomas, six giant cell tumors of the bone, three fibrosarcomas, and two Ewing's sarcomas. The mean follow-up was 5.6 years (2-10 years). The overall complication rate was 39%. Seven patients died of their disease, but none from complications related to the surgery. Five patients were revised to arthrodesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
62
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 16 publications
9
62
2
2
Order By: Relevance
“…The functional outcome can hardly be influenced positively even by using a connecting tube in proximal and total femur replacement. McGoveran et al [14] reported an MSTS score of 58.3%, and Ilyas et al [10] of 63.3% following proximal femur replacement nicely matching our results with 67%.…”
Section: Discussionsupporting
confidence: 81%
“…The functional outcome can hardly be influenced positively even by using a connecting tube in proximal and total femur replacement. McGoveran et al [14] reported an MSTS score of 58.3%, and Ilyas et al [10] of 63.3% following proximal femur replacement nicely matching our results with 67%.…”
Section: Discussionsupporting
confidence: 81%
“…These results compare well with those observed by Mittermayer et al, who observed a 5-year prosthetic survival of 79% and a 10-year survival of 71% [16]. Roberts et al reported a 5-year prosthetic survival of 74.9% [17], and Ilyas et al observed a 10-year prosthetic survival of 65% in a series of 48 patients [10].…”
Section: Discussionsupporting
confidence: 80%
“…Because malignant bone tumors are rare, reports about survivorship and complications of tumor endoprostheses generally are limited to small cohorts with relatively short followup [6,7,10,14,15] and commonly these investigations apply Kaplan-Meier estimations and Cox regression models to describe endoprosthetic survival. These analyses deal principally with one event as an endpoint, for example revision surgery, independent of its cause [20].…”
Section: Introductionmentioning
confidence: 99%